Theatre and Everyday Space: The Case of Tom Murphy - Hong, Moonyoung (Trinity College Dublin. School of English. Discipline of English, 2022)
The thesis investigates the relationship between modern theatre and everyday space, taking contemporary Irish playwright Tom Murphy (1935-2018) as a case study. Dramatising everyday life has been the focus of many playwrights, theatre-makers and practitioners, but the elusive category of the everyday has resulted in critical neglect of the concept as a frame of analysis. The everyday as a theatrical setting extends back to naturalism, which sought to represent it with scientific precision, starting in the domestic sphere: as Una Chaudhuri argues, the idea of home has preoccupied modern playwrights since the naturalist dramas of Henrik Ibsen and Anton Chekhov. This bourgeois domestic space created a new politics of the interior, where wider social issues of class, gender and family could be expressed onstage. Nevertheless, the foregrounding of home does not consider the multitude of other non-domestic everyday spaces that pervade the theatre. Murphy s works, which are deeply anchored in the spatiality of everyday locales a dancehall, a grocery store, a pub, a hotel, an office, a church, gasworks and airport offer a diverse range of other ( third ) spaces to be examined. In addition to examining the pressing philosophical questions raised by Murphy s dramatisation of everyday space, the thesis considers how his chosen spaces translate to the stage. Referring to the Murphy papers preserved in Trinity and various productions and performances from the archives in NUI Galway, the thesis provides a critically grounded and rounded picture of his theatre. In 2017, Murphy was awarded the title of Saoi, Aosdána s highest honour, in recognition of his remarkable contribution to Irish literature. Despite this legacy, there is a lack of scholarship focusing on his works. In engaging with his understudied works from a new perspective, the thesis examines Murphy s immense contribution to modern drama in general and Irish theatre in particular.
APPROVED
Keywords: Irish theatre; spatial theory; Tom Murphy; everyday; tragedy